Alcohol does not influence trust in others or oxytocin, but increases positive affect and risk-taking: a randomized, controlled, within-subject trial - Wenger, Leonard Paul; Hamm, Oliver; Mühle, Christiane; Hoffmann, Sabine; Reinhard, Iris; Bach, Patrick; Kornhuber, Johannes; Alpers, Georg W.; Kiefer, Falk; Leménager, Tagrid; Lenz, Bernd (European archives of psychiatry and clinical neuroscience, 2023)
Alcohol consumption to facilitate social interaction is an important drinking motive. Here, we tested whether alcohol influences trust in others via modulation of oxytocin and/or androgens. We also aimed at confirming previously shown alcohol effects on positive affect and risk-taking, because of their role in facilitating social interaction.
Gesehen am 02.11.2023